Improving Football Passing Skills in Physical Education Learning through Utilization of Audio Visual Media - Bernhardin, DinDin (Journal of Physical and Outdoor Education, 2023)
This study aims to determine whether learning physical education using audio-visual media can have a significant impact on improving students' football passing skills. This research is an experimental research with one group pretest-posttest design. The subjects of this study were students of MAN 2 Bandung. A total of 28 students of class X became the research sample after using the cluster random sampling technique. The passing skills test instrument was used to collect data in the study which was then analyzed using a paired sample t-test in the SPSS version 25 application. The results showed that the use of audio-visual media had a significant impact on students' passing skills in football. It can be concluded that audio-visual media is very suitable for use in physical education learning, especially in an effort to improve students' football passing skills